Isolasi dan Karakterisasi Ralstonia syzygii - Yanuar Danaatmadja; Siti Subandiyah; Tri Joko; Cavrina Ulita Sari (Universitas Gadjah Mada, 2009)
Ralstonia syzygii is one of important pathogens of cloves. This study was aimed at obtaining pure culture of R. syzygi from diseased plant tissue samples. The acterium was isolated from infected clove plantations in Ungaran, Central Java. It had the ability to make clove seedlings show symptoms and then die 41 days after inoculation. The reisolated bacterium also showed its ability to kill clove seedlings after 17 days. The bacterium is gram negative, able to ultilize glucose, sucrose, maltose, mannitol, sorbitol, dulcitol, and glycerol, able to hydrolyze starch, grow well at 27oC, able to catalyze and release water and oxygen from hydrogen peroxyde (H2O2) and aerobically.